Energy metabolism disorders in rare and common diseases. Toward bioenergetic modulation therapy and the training of a new generation of European scientists. (June 2015) - Rossignol, Rodrigue
Abstract: Energy metabolism alterations are found in a large number of rare and common diseases of genetic or environmental origin. The number of patients that could benefit from bioenergetic modulation therapy (BIOMET) is therefore very important and includes individuals with pathologies as diverse as mitochondrial diseases, acute coronary syndrome, chronic kidney disease, asthma or even cancer. Although, the alteration of energy metabolism is disease specific and sometimes patient specific, the strategies for BIOMET could be common and target a series of bioenergetic regulatory mechanisms discussed in this article. An excellent training of scientists in the field of energy metabolism, related human diseases and drug discovery is also crucial to form a young generation of MDs, PHDs and Pharma or CRO-group leaders who will discover novel personalized bioenergetic medicines, through pharmacology, genetics, nutrition or adapted exercise training. The Mitochondrial European Educational Training (MEET) consortium was created to pursue this goal, and we dedicated here a special issue of Organelle in Focus (OiF) to highlight their objectives. A total of 10 OiFs articles constitute this Directed Issue on Mitochondrial Medicine. As part of this editorial article, we asked timely questions to the PR. Jan W. Smeitink, professor of Mitochondrial Medicine and CEO of Khondrion, a mitochondrial medicine company. He shared with us his objectives and strategies for the study of mitochondrial diseases and the identification of future treatments. This article is part of a Directed Issue entitled: Energy Metabolism Disorders and Therapies.